FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAUAN UNTUK MEMBAYAR PAJAK PADA USAHA KECIL DAN MENENGAH DI SURABAYA - Widarto, Edwin; Shanti, Shanti; Tedjasuksmana, Budianto (Widya Mandala Surabaya Catholic University, 2013)
In order to maintain the governance and development of country, government needs fund that’s not a bit. One kind of the government’s income is tax. However, this big contribution isn’t followed by the willingness to pay taxes. On the other hand, the development of small and medium enterprises that so dynamic, become far and far away to be reached by taxation. The purpose of this empirical research is to test factors that influenced the willingness to pay taxes of SME in Surabaya. The independent varia-bles are consciousness of paying taxes, knowledge and understanding of tax laws, good perception of the effectiveness of the tax system, and the level of confidence in the government and legal system. The objects of research are SME that registered on Dinas Perdagangan dan Perindustrian Kota Surabaya, and also Dinas Usaha Mikro Kecil Menengah dan Koperasi Provinsi Jawa Timur which amounts to 101 SME. The research data obtained through distributing questionnaire to all object and the analysis using multiple linear regression. The result shows that good perception of the effectiveness of the tax system influence the willingness to pay taxes of SME. It shows that the effort given by the government to facilitate tax payments comes to effect. Meanwhile, con-sciousness of paying taxes, knowledge and understanding of tax laws, and the level of confidence in the government and legal system has no effect on the willingness to pay taxes.